Penerapan Strategi Pembelajaran Inkuiri untuk Meningkatkan Aktivitas dan Hasil Belajar Geometri pada Mahasiswa PGMI Universitas Islam Raden Rahmat Malang - Nanik Ulfa (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2018)
Geometry is one of the branches of mathematics thatare learned at the basic education level. Material geometryneed to be taught on a college student so have enough stock toteach mainly on mathematical subjects. To achieve thestandard ketuntasan minimum, then the learning process in theclassroom need to be designed according to the characteristicsof the students and the learning objectives to be achieved.Inquiry learning strategies chosen because according to thecharacteristics of the students who tend to be critical in theirthinking. This research was conducted to find out theeffectiveness of the learning strategy inkuiri in improvingstudent learning outcomes and activities. The methods used inthis research is classroom action research. The results of thisresearch show the cycle I learning activities reach 65% and theincrease in cycle II becomes 100%. For student learning resultsshowed improvement from the cycle I i.e. 57% to 91%. Studentlearning can be concluded in accordance with the minimumstandards set forth.